Clinical adverse events following COVID-19 vaccination: a scoping review of observational studies - Chango Rodríguez, Carlos Andres; Segovia Guerrero, Jorge Antonio; Huang Rivadeneira, Lia Camilie Chang; Cañar Robles, Ariana Marisol; Torres Cañarte, Paolo David; Moyano Salazar, Génesis Nathalie; Cañarte Moreira, Jessica Julieta; Loaiza Castro, Francisca Alejandra; Molina Recalde, Ana Paula; Alvarez Córdova, Verónica Maribel (International Journal of Research in Medical Sciences, 2025)
COVID-19 vaccination has been a central strategy to reduce severe disease and death during the pandemic. Although clinical trials demonstrated favorable safety profiles, real-world monitoring remains necessary to understand adverse reactions across diverse populations. Continuous post-authorization surveillance is essential to address concerns regarding vaccine safety and hesitancy. Objective of this study was to summarize observational evidence describing adverse reactions associated with COVID-19 vaccines in routine clinical and community environments. A scoping review was conducted following a structured methodological approach, including observational studies that evaluated post-vaccination adverse reactions. Eligible designs comprised cohort, registry-based and cross-sectional studies. Main outcomes included frequency, type, onset, severity and functional impact of adverse reactions. Eleven observational studies were included. The vaccines most frequently evaluated were Pfizer-BioNTech, Oxford-AstraZeneca, Moderna and Sinopharm. The most common reactions were local symptoms at the injection site, such as pain, tenderness and swelling, followed by systemic manifestations including fever, fatigue, headache, myalgia and chills. Most reactions appeared within the first 24 to 48 hours after vaccination, were mild or moderate in intensity and resolved spontaneously without medical intervention. Serious adverse events and fatal outcomes were uncommon, although isolated cardiovascular, neurological and allergic reactions were reported. Evidence from observational studies indicates that COVID-19 vaccines have a favorable real-world safety profile. Adverse reactions are predominantly mild, temporary and non-disabling. Continued transparent communication and post-marketing surveillance are necessary to maintain public confidence and ensure equitable uptake, particularly within vulnerable and underserved populations.